Fenologia, exigência térmica e produção de cultivares de videiras (Vittis spp.) em Lavras - MG - Carvalho, Edmilson de (2016)
The grapevine cultivation has great social, economic and cultural importance for several countries. In Brazil, the grape is produced mainly in the South, Southeast and Northeast regions. In the state of Minas Gerais, the cultivated area has growth significantly and today the projects are visible, both for wine and in natura, especially, based on results from research. The goal in this work was to characterize the phenological behavior, the thermal requirements (in degree-days) and the fruit production of nine grape cultivars for the region of Lavras-MG. The experiment was carried out in the experimental field of the Department of Agriculture / Fruit Sector, at the Campus of UFLA, in the crop season 2013/2014. The cultivars used in the trial were: Isabel, Concord, Bordô, BRS Cora, BRS Rúbea, Isabel Precoce, Concord Clone 30, BRS Violeta e Niágara Rosada, grafted on the ‘Paulsen 1103’ rootstock. The plants were cultivated in the espalier system. The trial was carried out in randomized blocks with three replicates, and twelve plants per plot, in rows in spaced 2,5m x 1,2m apart. The number of days, degree-day accumulation, pruning and fruit production (mean number of bunches per plant, average yield per plant, in each crop and for the three harvests) were evaluated. The cultivars Isabel Precoce and Violeta were the ones with the highest precocity, with a cycle of 107 days and accumulated 1200.7 degree-days. The cultivars Isabel and Concord were the later ones, needed 1512 degree-days with cycle of 130 days and 1483 degree-days with cycle 128 days, respectively. The cultivars BRS Cora and Isabel presented the best performance for the evaluated characters, while the cultivars Bordô, Concord, BRS Rúbea and Concord Clone 30 were inferior to the other cultivars.